Satellite Image Enhancement Using DWT and Gaussian Filter - Singh, Kshipra; Nair, Jijo S (International Journal of Computer Sciences and Engineering, 2025)
These days the image taken by the satellite generally utilized for differing applications however the element of these image degraded because of climate change, atmosphere and different elements are responsible. In image processing, an assortment of image enhancement methods have been produced for the satellite image restoration and improvement. This paper proposes an approach which utilizes DWT, Hybrid filter and Gaussian filter. The simulation of our anticipated technique is done utilizing the MATLAB2012a simulator which involves various functions for image enhancement and the similar examination of our strategy utilizes the execution measurements, for example, PSNR, EME and RMSE. The experimental consequences of our methodology give enhanced quality of image than the existing methods.